Novel diverse-structured h-WO3 nanoflake arrays as electrode materials for high performance supercapacitors. (20th February 2020) - Zheng, Feng; Wang, Jing; Liu, Wenbo; Zhou, Jianmin; Li, Hui; Yu, Yi; Hu, Pengfei; Yan, Wei; Liu, Yang; Li, Rong; Zhen, Qiang; Zhang, Jiujun
Abstract: Hexagonal tungsten trioxide (h-WO3 ) nano-materials can be widely used in many fields of optics, electrics and chemistry. In this work, three types of h-WO3 (single crystal, polycrystal and hierarchical) nanoflake arrays (WNFs) are synthesized through a simple hydrothermal method. The morphologies, crystalline degree and exposed faces of these WNFs can be controlled with simple adjustments of reaction parameters. The relationships between the crystal structures and supercapacitive properties of these WNFs are systematically investigated and the results show that: the single crystal WNFs with a fast electron transmitting channel exhibits a high rate performance at high voltage scan rate, while the polycrystal and hierarchical WNFs with more oxygen vacancies and ion storage spaces have relatively high specific capacitances at low scan rate. These WNFs are used to fabricate supercapacitors, which show specific energy density as high as 88.2 W h kg −1 at a power density of 400 W kg −1 . It is concluded that the electrode materials should have single structure facilitating the electrons transfer at current collector side and a porous structure for ion storage at the electrolyte side. Graphical abstract: Image 1 Highlights: Three different types of h-WO3 nanoflake arrays (WNFs) are synthesized on Cu foils. The WNFs has a high specific capacitance of 538 F g −1 at 0.5 A g −1 . The WNFs shows an energy density of 88.2 W h kg −1 at a power density of 400 W kg −1 . The single structure facilitates the electrons transfer at the current collector side. The porous structure could accommodate more ions at the electrolyte side.